Mediated climate rift society: articulation and metabolic rift theories in analyzing climate change news in South Africa - Evans, Henri-Count; Teer-Tomaselli, Ruth (Frontiers in Communication, 2023)
Journalism is essential in addressing climate change. Journalists’ constructions of climate change issues, worldviews and proposed solutions legitimise those aspects that are made commonsensical and are given discursive salience. The news media has often constructed climate change as a purely scientific issue whose solutions rely on technological interventions- thus neglecting climate change's cultural and political economics. This paper seeks to situate climate change journalism research within ecoCultural Studies and Environmental Sociology, specifically employing articulation and metabolic rift theories. To address this objective, the paper applies articulation and metabolic rift theories to examine how four weekly newspapers in South Africa reproduced neoliberal climate change solutions anchored on ‘green’ and ‘clean’ transition discourses. These discourses are represented as common-sensical and logical. In doing so, the newspapers reproduce dominant neoliberal discourses that seek to address climate change in ways anchored on profit-making. The paper argues that climate change is a product of capitalist exploitation and disruption. Articulation provides researchers with a means of identifying the different fragments that constitute discourse units in the news and also guards against the traps of capitalist essentialism and reductionism, instead allowing the researchers to account for ‘other factors’ and, in doing so, conceptualise how the articulation of the fragments leads towards making capitalism a ‘tendential force’ but born out of disjointed fragments. The metabolic rift theory remains central to understanding how capitalism has been an ecological force driving climate change. Therefore, the combination of articulation and the metabolic rift theories should be embraced as new ways of researching climate change in the news.